Monitoring Forest Carbon Sequestration with Remote Sensing - Du, Huaqiang; Fan, Wenyi; Li, Mingshi; Fan, Weiliang; Mao, Fangjie (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The forest, as the main body of the terrestrial ecosystem, has a huge carbon sink function and plays an important role in coping with global climate change. This reprint on "Monitoring forest carbon sequestration with remote sensing" mainly focuses on new remote sensing theories, methods, and technologies for monitoring carbon sinks in forest ecosystems (including urban forest ecosystems).